2007
DOI: 10.1152/ajplung.00418.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transiently, paralleled upregulation of arginase and nitric oxide synthase and the effect of both enzymes on the pathology of asthma

Abstract: Changes in the expression of arginase and their association with nitrosative stress were investigated using an asthmatic model previously established in NC/Nga mice with mite extract. Mite crude extract (100 microg/day) from Dermatophagoides farinae was administered intranasally for 5 consecutive days (day 0-4), and a single challenge was performed on day 11. On day 12, upregulation of the mRNA expression of inducible types of nitric oxide synthase (iNOS) and increases in immunohistochemical staining for iNOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 52 publications
(53 reference statements)
5
56
0
Order By: Relevance
“…Microarray analysis of gene expression in these models revealed that genes related to L-arginine metabolism, including the cytosolic isoform arginase I and the mitochondrial isoform arginase II, belonged to the most prominently overexpressed genes [22]. Increased arginase expression and activity in mouse lung has also been found in other studies, after challenge with either ovalbumin [50][51][52], Nippostrongylus brasiliensis [52], Schistosoma mansoni eggs [53], Dermatophagoides farinae [54] or trimellic anhydride [51]. In addition, ovalbumin increased arginase activity in the lungs of sensitised rats [55].…”
Section: +supporting
confidence: 60%
“…Microarray analysis of gene expression in these models revealed that genes related to L-arginine metabolism, including the cytosolic isoform arginase I and the mitochondrial isoform arginase II, belonged to the most prominently overexpressed genes [22]. Increased arginase expression and activity in mouse lung has also been found in other studies, after challenge with either ovalbumin [50][51][52], Nippostrongylus brasiliensis [52], Schistosoma mansoni eggs [53], Dermatophagoides farinae [54] or trimellic anhydride [51]. In addition, ovalbumin increased arginase activity in the lungs of sensitised rats [55].…”
Section: +supporting
confidence: 60%
“…Hematoxylin and eosin (H&E) staining was used to assess the degree of inflammation (16). Azan and periodic acid-Schiff (PAS) stainings were also done to observe interstitial collagen deposition and goblet cell hyperplasia, respectively (35). The levels of inflammation in peribronchial and perivascular spaces of the lung were determined by an ordinal scale ranging from 0 to 3, as described elsewhere (36).…”
Section: Bronchoalveolar Lavage Fluidmentioning
confidence: 99%
“…In various mouse and rat models, it has been confirmed that allergen challenge causes a considerable increase in the expression and activity of particularly arginase type I, most probably via Th2 cytokines involved in the asthmatic airway inflammation [120][121][122][123][124][125][126][127]. Notably, by microarray analysis of gene expression in Balb/c mice sensitised to ovalbumin or Aspergillus fumigatus, it was shown that, among the 291 common genes that were induced by these allergens, enzymes involved in L-arginine metabolism, particularly arginase I and II, belonged to the most predominantly overexpressed genes [127].…”
Section: Acute Modulation Of Ahrmentioning
confidence: 99%